2012
DOI: 10.4261/1305-3825.dir.6113-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standardized uptake values obtained from 18f fluorodeoxyglucose positron emission tomography/computed tomography imaging performed with 2d and 3D modes in oncological cases

Abstract: NUCLEAR MEDICINEORIGINAL ARTICLE PURPOSE We investigated the usability of standardized uptake values (SUV) obtained from both two-and three-dimensional (2D and 3D) positron-emission tomography and computed tomography (PET-CT) imaging, and compared the images obtained from these techniques in terms of image quality, lesion detectability, and the presence of artifacts. MATERIALS AND METHODSImage data from 100 patients, who had undergone two PET imagings obtained in 2D and 3D mode after a low dose CT, were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In the current work we found that SUV mean and SUV (std/mean) were smaller in 3D than in 2D mode, whereas, [28]. In the current work we found that SUV mean and SUV (std/mean) were smaller in 3D than in 2D mode, whereas SUV max was a little larger in 2D mode than in 3D mode.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In the current work we found that SUV mean and SUV (std/mean) were smaller in 3D than in 2D mode, whereas, [28]. In the current work we found that SUV mean and SUV (std/mean) were smaller in 3D than in 2D mode, whereas SUV max was a little larger in 2D mode than in 3D mode.…”
Section: Discussionsupporting
confidence: 51%
“…Kocabaş et al . reported that SUV max was variable between 3D and 2D modes and the values were smaller in 3D mode [ 28 ]. In the current work we found that SUV mean and SUV (std/mean) were smaller in 3D than in 2D mode, whereas SUV max was a little larger in 2D mode than in 3D mode.…”
Section: Discussionmentioning
confidence: 99%